2022
DOI: 10.1016/j.teln.2022.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Community college students’ perspectives on online learning during COVID-19 and factors related to success

Abstract: This study's purpose was to research trends in community college students' perceptions of online learning during the COVID-19 pandemic and discover factors related their success, applying this knowledge to nursing education. Community college students (N=156) participated in the 34-question survey that asked questions related to perception of online learning, instructor involvement and characteristics of success. Thirty-seven percent of the sampling self-reported that they were nursing or allied health majors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…Tanggal 2 Maret 2020 merupakan hari yang mencengangkan bagi bangsa Indonesia, karena pada tanggal ini warga Indonesia untuk pertamakalinya mengumumkan kasus virus corona (Penrod et al, 2022). Sampai pada bulan Mei 2020, terdapat 31.024 kasus virus corona yang tersebar pada 34 provinsi diseluruh penjuru Indonesia (Gugus Tugas Percepatan Penanganan Virus Corona, 2020).…”
Section: Pendahuluanunclassified
“…Tanggal 2 Maret 2020 merupakan hari yang mencengangkan bagi bangsa Indonesia, karena pada tanggal ini warga Indonesia untuk pertamakalinya mengumumkan kasus virus corona (Penrod et al, 2022). Sampai pada bulan Mei 2020, terdapat 31.024 kasus virus corona yang tersebar pada 34 provinsi diseluruh penjuru Indonesia (Gugus Tugas Percepatan Penanganan Virus Corona, 2020).…”
Section: Pendahuluanunclassified
“…A study conducted during the epidemic showed that online learning outcomes for community college working nursing and health students were strongly correlated with ages of students, faculty support, and effective communication styles. [27] Therefore, in addition to the prior planning of online teaching courses, teachers must be involved during its implementation process to understand the completion of learning activities, especially when the students are working students who may miss some learning activities due to their work.…”
Section: The Effectiveness Of Online Teaching Versus Face-toface Teac...mentioning
confidence: 99%
“…Traditional classrooms were built with a factory-style instructional method in mind, which may have fitted the needs of the time. Therefore, they are not equipped to handle today's technological demands or to educate pupils with a variety of working methods and thinking processes [1]. Virtual learning environments (VLEs) or VR classrooms might help bridge this gap.…”
Section: Introductionmentioning
confidence: 99%